Badania Zakładu Historii Oświaty i Wychowania Wydziału Pedagogicznego Uniwersytetu Warszawskiego nad myślą pedagogiczną XIX i XX wieku prowadzone w latach 2013–2016 - Kamińska, Janina (Biuletyn Historii Wychowania, 2016)
Between 2013 and 2016 the Department of the History of Education at the Faculty of Education (University of Warsaw) carried out research on the pedagological thought of the 19th and 20th centuries. It was mainly centered on the pedagological legacy of Aniela Szycówna (1869–1921), Iza Moszczeńska (1864–1941), Jan Hulewicz (1907–1980), Anna Mońka-Stanikowa (1917–2007) and Anna Radziwiłł (1939–2009). It is worthwhile to start investigating other personas that shaped the Polish education, as well as the legacy of other pedagogues who addressed educational problems in their research. Without doubt, such studies require investigating sources. Information can be found, for example, in articles published in educational journals, such as Przegląd Pedagogiczny, Kwartalnik Pedagogiczny (published at the beginning of the 20th c.), along with more recent periodicals focused on education and its history.